Aging-Related Accumulation of Truncated Oxidized Phospholipids Augments Infectious Lung Injury and Endothelial Dysfunction via Cluster of Differentiation 36-Dependent Mechanism - Yunbo Ke; Pratap Karki; Yue Li; Kamoltip Promnares; Chen-Ou Zhang; Thomas L. Eggerman; Alexander V. Bocharov; Anna A. Birukova; Konstantin G. Birukov (Cells, 2023)
Truncated phospholipid oxidation products (Tr-OxPL) increase in blood circulation with aging; however, their role in the severity of vascular dysfunction and bacterial lung injury in aging groups remains poorly understood. We investigated the effects of six Tr-OxPL species: KOdiA-PC, POVPC, PONPC, PGPC, Paz-PC, and Lyso-PC on endothelial dysfunction and lung inflammation caused by heat-killed Staphylococcus aureus (HKSA) in young (aged 2–4 months) and old (aged 12–18 months) mice, organotypic culture of precisely cut lung slices, and endothelial cells (mLEC) isolated from young and old mice. HKSA and Tr-OxPL combination caused a higher degree of vascular leak, the accumulation of inflammatory cells and protein in bronchoalveolar lavage, and inflammatory gene expression in old mice lungs. HKSA caused a greater magnitude of inflammatory gene activation in cell and ex vivo cultures from old mice, which was further augmented by Tr-OxPLs. L37pA peptide targeting CD36 receptor attenuated Tr-OxPL-induced endothelial cell permeability in young and old mLEC and ameliorated KOdiA-PC-induced vascular leak and lung inflammation in vivo. Finally, CD36 knockout mice showed better resistance to KOdiA-PC-induced lung injury in both age groups. These results demonstrate the aging-dependent vulnerability of pulmonary vasculature to elevated Tr-OxPL, which exacerbates bacterial lung injury. CD36 inhibition is a promising therapeutic approach for improving pneumonia outcomes in aging population.